New insights into chronic ankle instability: an in vivo evaluation of three-dimensional motion and stability of the ankle joint complex - Wang, Shengli; Ruan, Yaokuan; Wang, Kaize; Chang, Fei; Chen, Boya; Zhang, Nan; Qian, Zhihui; Ren, Lei; Ren, Luquan (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionChronic ankle instability (CAI) is generally associated with repetitive ankle sprains with concomitant ligament injuries and abnormal joint motion, which affects the stability of the joint. This study aims to quantify and compare the 3D motion differences in the ankle joint complex (AJC) during walking between CAI patients and healthy controls and to analyze the effect of CAI on the vertical ground reaction force (vGRF) and center of pressure (COP) distribution.MethodsFifteen CAI patients (6 males, 9 females; height 165 ± 3.8 cm; weight 68.5 ± 10.2 kg; BMI 21.6 ± 3.5 kg/m2) with anterior talofibular and calcaneofibular ligament sprains and fifteen healthy participants (8 males, 7 females; height 168 ± 4.2 cm; weight 74.5 ± 12.6 kg; BMI 22.3 ± 4.2 kg/m2) participated in this study. Dynamic biplanar radiography were used to analyze the 3D motion and stability of the ankle joint complex during the stance phase. Synchronous force plate data were used to assess vGRF and COP trajectories.ResultsCompared to controls, CAI patients showed increased plantarflexion (1.3°), internal rotation (2.0°), and medial translation (0.6 mm) in the tibiotalar joint, along with decreased dorsiflexion (3.0°). For the subtalar joint, plantarflexion decreased (1.8°), and external rotation increased (0.9°). The tibio-calcaneal joint showed increased internal rotation (1.9°) and posterior translation (0.5 mm). Stability differences included more dispersed axes of rotation and greater spatial motion volumes of landmarks in the CAI group. Additionally, CAI patients exhibited greater peak vGRF with earlier peaks, higher loading rates, and more lateral and unstable COP trajectories.ConclusionThese findings reveal that CAI not only alters the 3D motion and stability of the AJC but also affects foot-ground interaction forces, such as vGRF and COP distribution, during walking. This study provides critical insights into the altered biomechanics of the AJC in CAI patients and contributes to the clinical diagnosis of CAI and evaluation of results from surgical or conservative intervention.